Economic Growth in Malaysia: A Causality Study on Macroeconomics Factors (Journal of Entrepreneurship and Business, 2021)
The volatile state of economic growth has long been the theme of studies among researchers. Past findings associate a number of factors behind the fluctuation in economic growth in varying degrees. In this study, four macroeconomic variables, namely oil prices, foreign direct investment (FDI), exports, and inflation are particularly selected to test their relationship and impact on the economic growth of Malaysia, as measured using Gross Domestic Product (GDP). By utilizing time series data from 1976 to 2016, a series of empirical analysis including the Augmented-Dickey Fuller (ADF) and Phillip Peron (1988) unit root assessment, Johansen and Juselius test of cointegration and Granger causality analysis are employed to assess the direction of impact and long-run relationships between the variables. Our findings reveal there is a long-run impact among them. While oil prices, foreign direct investment, and export are significant to influence economic growth, there is no indication of causality between inflation on any of the variables.
Keywords: Array; Array; Array; Array